1976
DOI: 10.1097/00006842-197609000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Body Image Disturbances in Anorexia Nervosa and Obesity

Abstract: Measures were made of body image and personality features in patients with anorexia nervosa and obesity. It was hypothesized that obese and anorexic patients would display similar body image disturbances characterized by relative overestimation of body size in comparison with control subjects. Body image was measured by both a distorting photograph technique (a general measure) and a visual size estimation apparatus (for specific body regions). Personality features were assessed by the Eysenck Personality Inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
128
0
3

Year Published

1978
1978
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 226 publications
(140 citation statements)
references
References 0 publications
9
128
0
3
Order By: Relevance
“…Moreover while anorexic and obese subjects have been shown to overestimate their sizes, this tendency has been observed in normal (21,35,94), pregnant (94), thin and neurotic women (35), and schizophrenics (29). Although these observations do not negate the diagnostic and prognostic utility of this measurement technique, they raise important questions about the precise meaning of body image findings derived from studies using the caliper device.…”
Section: Body Imagementioning
confidence: 96%
See 3 more Smart Citations
“…Moreover while anorexic and obese subjects have been shown to overestimate their sizes, this tendency has been observed in normal (21,35,94), pregnant (94), thin and neurotic women (35), and schizophrenics (29). Although these observations do not negate the diagnostic and prognostic utility of this measurement technique, they raise important questions about the precise meaning of body image findings derived from studies using the caliper device.…”
Section: Body Imagementioning
confidence: 96%
“…Fries (29) and Goldberg et al (40) confirmed a self-overestimation tendency in anorexic subjects when compared to controls. On the other hand, Crisp and Kalucy (21) and Garner et al (35) observed selfoverestimation of body regions in controls as well as eating disorder groups. Similarly, Slade and Russell (95) have reported the caliper device was able to differentiate obese from normals but this was in contrast with studies using a similar measure (16,21,35).…”
Section: Body Imagementioning
confidence: 96%
See 2 more Smart Citations
“…include techniques such as the distorting mirror (Traub & Orbach, 1964), projection of photographs with distorting lenses (Garner, Garfinkel, & Bonato, 1987;Garner, Garfinkel, Stancer, & Moldofsky, 1976;Glucksman & Hirsch, 1969), the video-distortion technique (Allebeck, Hallberg, & Spamark, 1976;Askevold, 1975;Fernández-Aranda, Dahme, & Meermann, 1999;Freeman, Thomas, Solyom, & Hunter, 1984;Meermann & Vandereycken, 1988;Probst, Van Coppenolle, Vandereycken, & Goris, 1992;Smeets, Ingleby, Hoek, & Panhuysen, 1999), the life-size screen distortion method (Gardner & Bokenkamp, 1996;Probst, Van Coppenolle, Vandereycken, Kampman, & Goris, 1991;Probst, Vandereycken, & Van Coppenolle, 1997;Probst, Vandereycken, Van Coppenolle, & Vanderlinden, 1995), and the silhouette method (Bell, Kirkpatrick, & Rinn, 1986;Furnham & Alibhai, 1983).…”
mentioning
confidence: 99%